2009
DOI: 10.1523/jneurosci.2781-08.2009
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of TRPC Channels in CCL2-Mediated Neuroprotection against Tat Toxicity

Abstract: Chemokine (C-C motif) ligand 2 (CCL2), also known as monocyte chemoattractant protein-1, plays a critical role in leukocyte recruitment and activation. In the present study, we identify an additional role for CCL2 that of neuroprotection against HIV-1 transactivator protein (Tat) toxicity in rat primary midbrain neurons. Furthermore, we report the involvement of transient receptor potential canonical (TRPC) channels in CCL2-mediated neuroprotection. TRPC are Ca 2ϩ -permeable, nonselective cation channels with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…The secondary antibodies were alkaline phosphatase conjugated to goat anti mouse/rabbit IgG (1:5000) as described previously. 19 …”
Section: Western Blottingmentioning
confidence: 99%
“…The secondary antibodies were alkaline phosphatase conjugated to goat anti mouse/rabbit IgG (1:5000) as described previously. 19 …”
Section: Western Blottingmentioning
confidence: 99%
“…Ca 2+ influx through TRPC channels appears to be a critical component of the signaling cascade that mediates growth cone guidance and survival of neurons in response to several growth factors (47,48). In particular, recent studies have shed light on the neuroprotective effect of TRPC channels in the SNpc against Tat neurotoxicity (49). Our previous studies also show the neuroprotective action of TRPC1 against in vitro cell culture models of PD (19); however, the precise mechanisms by which TRPC1 regulates neuronal survival remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have shown that ␣CCL2 neutralizing antibody significantly reduced CXCL16 neuroprotection. The ability of CCL2 to preserve neuronal cell death by other insults, such as HIV-1 trans-activator protein (Tat) toxicity, has been documented (Yao et al, 2009). Moreover the hypothesis that CCL2 can act as a critical intermediate factor driving neuroprotection is consistent with the findings that, in human cortical neuronal cultures, CCL2 released by astrocytes, upon RANTES stimulation, reduces the toxic effect of NMDA and Tat (Eugenin et al, 2003), and with recent data showing that astrocyte-derived CCL2 mediates the neuroprotective effect of noradrenaline against excitotoxic and OGD damages (Madrigal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%